Stress Urinary Incontinence Treatment Using Vaginal Fractional CO2 Laser (10600nm) - Ibrahim, Nadia A.; Awazli, Lutfi G. (Iraqi Journal of Laser, 2020)
Stress urinary incontinence (SUI) is involuntary urine leakage during activities that increase abdominal pressure such as coughing, sneezing and lifting of heavy weights. This is a very common disorder among women with history of multiple vaginal deliveries with an obstructed labor. SUI is considered one of the most distressing problems, especially for younger women, with severe quality of life implications, it caused by the loss of urethral support, usually as a consequence of the supporting structural muscles in the pelvis. Objective: To prove and demonstrate the effect of a fractional CO2 micro-ablative laser (10600nm) in intra vaginal therapy for treating SUI and achieve a clinical improvement of the urogenital system support. Methods: This is a prospective, observational study which was conducted over six month from the 1st . of July to 29th of December 2016 in Consultation Gynecologist Clinic in Al-Hila city, Iraq, in patients who complain of SUI. Twenty female patients were included in the study, their age ranged from 30- 69 year, at range (49.5 year ) fifteen patient delivered vaginally, two delivered by cesarean section, two had combined delivery and one was Nulliparous ,all of them received the same treatment protocol. Detailed history about continence assessment, quality of life and sexuality before and after therapy. The fractional CO2 Aphrodite laser was used. The parameters used in each session were energy/(dot)pixel 119.4mJ, pulse duration 900 μs, frequancy1000Hz, and exposure time 300ms /shot with average of shots 34 and in range 26-42, in three sessions four weeks apart between them. The patients were followed for three months started from the beginning of the second session to one month after the last session. Results: Thirty-five percent of patients 35%(n=7) were cured ,and these 35% included all patients delivered by cesarean section and one third of patients who delivered vaginally and extensively most of patients were 60%(n=12) improved of their SUI. Patient reported no leakage any more while coughing or sneezing. Only 5%(n=1) not responded was menopause women. Conclusions: This study shows that micro-ablative fractional CO2 laser is effective can produce a remodeling of vaginal connective tissue without causing damage to surrounding tissue and the group of patients with continence disorder without vaginal delivery achieved marked improvement .